The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1891/2168-6653.28.1.24
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Validation of the Internal and External Motivation to Respond Without Prejudice Toward People With Disabilities Scale

Abstract: Objective: To determine the factorial validity of the Internal and External Motivation to Respond without Prejudice toward People with Disabilities Scale (D-IMS/EMS).Design: A quantitative descriptive design using factor analysis.Participants: 233 rehabilitation counseling and rehabilitation services students.Results: Both exploratory and confirmatory factor analysis provided evidence for the 2-factor structure of the D-IMS/EMS. The internal motivation and external motivation factors were found to correlate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Our results have robustly replicated the psychometric qualities of the IEMS scale (Plant & Devine, 1998;Klonis, Plant, & Devine, 2005;Pruett et al, 2014). Specifically, in both PCA and CFA, and across both social groups against which motivations to avoid prejudice were rated, we consistently observed that IEMS items clustered into two meaningful factors resembling two uncorrelated constructs reflecting internal and external reasons to avoid prejudiced thoughts and behaviors.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results have robustly replicated the psychometric qualities of the IEMS scale (Plant & Devine, 1998;Klonis, Plant, & Devine, 2005;Pruett et al, 2014). Specifically, in both PCA and CFA, and across both social groups against which motivations to avoid prejudice were rated, we consistently observed that IEMS items clustered into two meaningful factors resembling two uncorrelated constructs reflecting internal and external reasons to avoid prejudiced thoughts and behaviors.…”
Section: Discussionsupporting
confidence: 73%
“…Although the scale was originally developed to account for individual differences in intergroup bias against Blacks, it was adapted to evaluate internal and external motivations to withhold prejudice toward other minorities or marginalized social groups as well (Klonis, Plant, & Devine, 2005;Pruett, Deiches, Pfaller, Moser, & Chan, 2014). However, its psychometric properties have not been tested on population samples outside the United States, which is substantially different from regions of middle/eastern Europe in terms of cultural and historical experience with minorities.…”
Section: Present Researchmentioning
confidence: 99%